UJI AKTIVITAS ANTI-AGING KRIM TABIR SURYA KOMBINASI EKSTRAK TONGKOL JAGUNG (Zea mays L.) DAN EKSTRAK BIJI KOPI ROBUSTA (Coffea canephora Pierre Ex. A. Froehner) - Harpolia Cartika; Yetri Elisya; Fatwa Hasbi; Khairun Nida (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Skin aging which is characterized by wrinkles and reduced skin moisture due to sun exposure can be prevented by using sunscreen preparations. The sunscreen cream combination of corn cob extract and robusta coffee bean extract has strong antioxidant activity and extra protection, so it has the potential as anti-aging. This study aims to determine the anti-aging activity of the test cream. Research using experimental methods. The sunscreen cream contains 10% corn cob extract and 15% robusta coffee bean extract. Physical testing and cream stability using the cycling test method. The anti-aging activity of the cream was tested in vivo using female Sprague-Dawley rats, the observations were continued by SEM, the parameter was wrinkles. The results of the evaluation of physical stability meet the requirements of the cream. Details of the average score of wrinkles on the skin of the feet of rats given a cream base of 2.5, a test cream of 1.5 and a comparison cream of 1. This indicates the test cream has the potential as an anti-aging.